Up-regulation of interferon-stimulated gene15 and its conjugates by tumor necrosis factor-α via type i interferon-dependent and -independent pathways - Kongthawat Chairatvit (2018)
Interferon-stimulated gene15 (ISG15) is the first characterized ubiquitin-like protein, which is strongly induced by type I interferons (IFN-α/b), bacterial endotoxin, and cellular stress. Up-regulation of ISG15 is observed in several cancer cell types and is associated with cancer progression. As many cytokines can influence all stages of tumorigenesis, the elevated expression of ISG15 system may be regulated in cancer cells by inflammatory cytokines. In this study, we showed that TNF-α, but not TGF-β and IL-6, up-regulates levels of both ISG15 and its conjugates in human lung carcinoma A549 and human squamous carcinoma HSC4 cell lines. Induction of ISG15 and its conjugates by TNF-α was dose-dependent and required mediation of p38 MAP kinase and Jak1 through up-regulation of endogenous type I interferon expression. SB202190 (p38 MAPK inhibitor) and Jak1 inhibitor suppressed TNF-α-induced expression of ISG15 and its conjugates. However, only SB202190 inhibited the expression of type I interferons by TNF-α. Although B18R, a soluble type I interferon receptor, totally abolished the effect of exogenous IFN-β, it was unable to inhibit completely the TNF-α-induced ISG15 production. In addition, the initiation of ISG15 induction by TNF-α was detected earlier than that of IFN-b induction. Taken together, TNF-α elicits the induction of ISG15 and ISG15 conjugates not only via the autocrine stimulation of type I interferon expression, but also through a type I interferon-independent pathway. These data provide a possible link between inflammatory response and cancer progression. © 2012 Springer Science+Business Media, LLC.